2005
DOI: 10.1097/01.bto.0000177737.60532.ff
|View full text |Cite
|
Sign up to set email alerts
|

The WasherLoc and Bone Dowel: A Rigid, Slippage-Resistant Tibial Fixation Device for a Soft Tissue Anterior Cruciate Ligament Graft

Abstract: The WasherLoc is a tibial fixation device for soft tissue anterior cruciate ligament (ACL) reconstruction that combines superior fixation properties (945 N strength, 507 N/mm stiffness, and high resistance to slippage) with a simple surgical technique. The WasherLoc is a washer with 13 short spikes that penetrate the soft tissue ACL graft in multiple locations and 4 long peripheral spikes that contain the graft beneath the washer. A cancellous screw is used to compress the WasherLoc against the soft tissue ACL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The use of a prosthetic ligament would allow an earlier mechanical load as compared to the biological autograft or allograft. However, to obtain this type of stabilization it was necessary to solve some mechanical problems, well known in the human surgery, the most important being the method of fixation of the artificial ligament, particularly at the tibial site, that is considered the weakest link of the entire implant [ 8 , 13 , 14 , 15 , 22 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of a prosthetic ligament would allow an earlier mechanical load as compared to the biological autograft or allograft. However, to obtain this type of stabilization it was necessary to solve some mechanical problems, well known in the human surgery, the most important being the method of fixation of the artificial ligament, particularly at the tibial site, that is considered the weakest link of the entire implant [ 8 , 13 , 14 , 15 , 22 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its traction resistance is dependent on the quality of the metaphyseal bone, and some studies have suggested that some additional fixation should be used in order to achieve successful ligament reconstruction (31) . Hill et al (31) proposed that cortical staples should be used, while other authors have suggested using intratunnel bone grafts 32 , 33 and additional care with the technique at the time of inserting the screw, so that the graft tension is not lost, as put forward by Grover et al (34) .…”
Section: Discussionmentioning
confidence: 99%